2007
DOI: 10.1080/08830180601070179
|View full text |Cite
|
Sign up to set email alerts
|

TheIn VivoResponse of Invariant Natural Killer T Cells to Glycolipid Antigens

Abstract: Invariant natural killer T (iNKT) cells are a subset of T lymphocytes that recognizes glycolipid antigens presented by the major histocompatibility complex class I-related protein CD1d. Although iNKT cells have received a lot of attention as targets for the development of immunotherapies, few studies have investigated the in vivo response of iNKT cells to glycolipid antigen activation. Accumulating evidence indicates that iNKT cells generate a dynamic response to in vivo activation by glycolipid antigens that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…iNKT cell hyporesponsiveness induced by bacteria exhibited a number of similarities to iNKT cell anergy induced by α-GalCer (15). First, as already discussed, iNKT cell hyporesponsiveness correlated with sustained NK1.1 downregulation by splenic iNKT cells ( Figure 1B), and we observed a similar downregulation of the activating NK cell receptor NKG2D and the CD94 subunit of the NKG2/CD94 family of NK cell receptors (Supplemental Figure 3).…”
Section: ) Enterococcus Faecalis (Data Not Shown) and Streptococcussupporting
confidence: 56%
See 2 more Smart Citations
“…iNKT cell hyporesponsiveness induced by bacteria exhibited a number of similarities to iNKT cell anergy induced by α-GalCer (15). First, as already discussed, iNKT cell hyporesponsiveness correlated with sustained NK1.1 downregulation by splenic iNKT cells ( Figure 1B), and we observed a similar downregulation of the activating NK cell receptor NKG2D and the CD94 subunit of the NKG2/CD94 family of NK cell receptors (Supplemental Figure 3).…”
Section: ) Enterococcus Faecalis (Data Not Shown) and Streptococcussupporting
confidence: 56%
“…In sharp contrast, little is known regarding the immune response mediated by glycolipid-reactive, CD1d-restricted iNKT cells. We and others have shown that treatment of mice with the potent iNKT cell agonist α-GalCer results in the rapid activation and proliferation of these cells, followed by homeostatic contraction of the iNKT cell population and acquisition of an anergic phenotype (15). Here we have demonstrated that iNKT cells activated in response to multiple bacterial microorganisms acquire a similar hyporesponsive phenotype, which can significantly impact subsequent iNKT cell-mediated immune responses and the efficacy of iNKT cell-based immunotherapy.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The cytokines secreted by activated iNKT cells amplify the immune response initiated by these cells through transactivation of other cell types, including DCs, macrophages, NK cells, B cells and conventional CD4 and CD8 T cells [75–79]. This is evidenced by rapid upregulation of the activation marker CD69 or NK and B and T cells, and by induction of various costimulatory molecules on DCs, macrophages and B cells, following in vivo injection of α-GalCer.…”
Section: Inkt Cell Responses To Glycolipid Antigensmentioning
confidence: 99%
“…15 Following TCR engagement, iNKT cells rapidly produce a variety of cytokines and exhibit cytotoxic activity. 16,17 One unusual property of iNKT cells is their capacity to produce mixtures of cytokines typically associated with either pro-inflammatory [e.g. interferon-c (IFN-c) 19 and several subsets of regulatory iNKT cells.…”
Section: Invariant Nkt Cellsmentioning
confidence: 99%